The Perceptions between Teachers’ in Public and Private Schools related to the (LFH) Learn from Home Policy - Sari Wahyuni; Ariyanti Ariyanti (Borneo Educational Journal (Borju), 2020)
Knowledge of the various kinds of teacher perceptions between 2 different schools about LFH policies will increase our knowledge of each teacher's strengths and weaknesses in learning activities using LFH policies during the pandemic. This research was conducted in private schools SD Darul Falah 2 Samarinda and public schools SDN 019 Muara Badak, namely four teachers and two principals. It collected data in this study using interview techniques to determine the strengths and weaknesses of LFH policies from teacher perceptions of LFH policies and questionnaire techniques to support interviews with teachers. Furthermore, The results showed that 24% of private school teachers' perceptions of the LFH policy were included in the "Disagree" category. Similar to private schools, the results showed that public school teachers' perceptions of LFH policies, namely 23.5%, were also included in the "Disagree" category. From these two results, it can be concluded that the average teacher disagrees with the LFH policy because it is considered to have many deficiencies that can impact current education development. The data subject was challenged to face in the learning process because the situation made students and teachers need a high focus level to understand what was conveyed by the teacher in daring or online learning.